Effects of 2-chloroadenine substitution in DNA on restriction endonuclease cleavage reactions. - Hentosh, P (1991)
The purine analog, 2-chloro-2'-deoxyadenosine triphosphate (CldATP), was incorporated enzymatically in place of dATP into the minus strand of M13mp18 duplex DNA. Its effect on protein-DNA interactions was assessed by determining the amount of DNA cleavage by type II restriction endonucleases. Substitution of chloroadenine (CIAde) for adenine (Ade) in DNA appreciably decreased the amount and rate of DNA cleavage of the minus strand when the analog was situated within the appropriate endonuclease recognition site. CIAde residues flanking a restriction site had variable effects. SmaI cleaved both CIAde-containing and control substrates with equal efficiency. NarI, however, was stimulated 1.5-fold by the presence of CIAde outside its recognition site. The effects of analog incorporation on restriction enzyme cleavage of an opposing unsubstituted strand of duplex DNA was examined by enzymatically incorporating CIdATP into the complementary minus strand of a 36-base oligonucleotide. Endonucleolytic cleavage of both plus and minus strands was reduced on 36-mers containing CIAde residues located within only the minus strand. These data suggest that CIAde residues incorporated into a single DNA strand may have an appreciable effect on DNA-protein interactions that involve one or both strands of duplex DNA.